Germinoma of the Pineal region in a Paediatric Immunocompromised Host: A Case Report (GAIMS Journal of Medical Sciences, 2026)
Pineal region tumors constitute 0.4 to 1% of all intra-cranial neoplasms, with germinomas being the most common subtype, predominantly affecting adolescent males. Their occurrence in young children with concurrent immunocompromise is exceptionally rare and diagnostically challenging.A 9-year-old HIV positive male on anti-retroviral therapy (ART) presented with a two-month history of intermittent holocranial headache. Neuro-imaging revealed a 2.5 x 3.1 x 3.2 cm heterogenous pineal region mass with obstructive hydrocephalus. FDG-PET/CT demonstrated intense focal uptake (SUVmax 24.2) without systemic metastatic disease. Cerebrospinal fluid (CSF) analysis showed lymphocytic pleocytosis with markedly elevated lactate dehydrogenase (LDH: 77 IU/L). Histopathological examination of biopsy tissue revealed large polyhedral cells with prominent nucleoli arranged in sheets, associated with dense fibrous stromal lymphocytosis. Immunohistochemistry (IHC) confirmed positivity for c-KIT (CD-117) and podoplanin (D2-40), establishing a final diagnosis of intra-cranial/pineal germinoma.This case highlights the diagnostic complexity of pineal germinoma in an immunocompromised pediatric patient, where overlapping pathologies must be carefully excluded. Integration of advanced neuroimaging, CSF biochemistry, histopathology, and IHC is essential for definitive diagnosis. The radiosensitive nature of germinoma, if confirmed on molecular staging, offers a favorable prognosis with appropriate chemo-radiotherapy.